KEMISKINAN DAN KETAHANAN PANGAN RUMAH TANGGA TANI DI SUB DAS KEDUANG KABUPATEN WONOGIRI - , AJENG AYU NABILLA MANDALA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to know human assets, natural, physical, financial, and social, to identify level of poverty and food security in critical and non critical land areas, to analyze factors affecting level of food security, to identify linkages between poverty and food security. The research was conducted in Keduang Subwatershed Wonogiri District, determined purposively covering upstream, midstream, and downstream which describes the land area of critical and non critical. The respondents are 120 farmers, randomly selected with 20 farmers in each location. The results show that human assets (age, education, farming experience, number of household), natural (land area, tree assets), physical (vehicles), financial (savings, jewelry, cattle), social (solidarity, trust and cooperation, conflict resolution) in the critical land areas are similar to the non critical, while agricultural equipment in critical land areas is lower than the non critical. Poverty in the critical is higher than the non critical areas based on criteria Sajogyo, World Bank, Asian Development Bank (ADB), and the Food and Agriculture Organization (FAO), whereas according to the criteria of BPS Wonogiri District in areas of critical and non critical land not classified as poor. Food security in critical is lower than the non critical areas. Factors affecting food security are education, land area, number of household, food expenditure, non food expenditure. Poverty and food security are intertwined, percentage of vulnerable households within non poor households are found enough high where sometime the vulnerable household be able to change into insecure category if the food supply is not sufficient.